Crystal structure of the zinc‐bound HhoA protease from Synechocystis sp. PCC 6803. Issue 19 (23rd September 2016) - Dong, Wei; Wang, Jia; Niu, Guoqi; Zhao, Shun; Liu, Lin
Abstract : The high temperature requirement A (HtrA) proteases are oligomeric serine proteases essential for protein quality control. HtrA homolog A (HhoA) from the photosynthetic cyanobacterium Synechocystis sp. PCC 6803 assembles into a proteolytically active hexamer. Herein, we present the crystal structure of the hexameric HhoA in complex with the copurified peptide. Our data indicate the presence of three methionines in close proximity to the peptide‐binding site of the PDZ domain. Unexpectedly, we observed that a zinc ion is accommodated within the central channel formed by a HhoA trimer. However, neither calcium nor magnesium showed affinity for HhoA. The role of the zinc ion in HhoA was tested in an in vitro proteolytic assay against the nonspecific substrate β‐casein and was found to be inhibitory. Our findings provide insights into the regulation of HhoA by a redox‐related mechanism involving methionine residues and by zinc ion‐binding within the central channel. Abstract :